Features of Pedagogical Management of Students Civil and Patriotic Qualities Forming - Kozhanova, Marina B.; Kozhanov, Igor V.; Ibraeva, Gulnara R.; Komelina, Valentina A.; Krylov, Dmitry A.; Kuzmin, Nikolai V.; Golovina, Nadezhda N.; Arefeva, Svetlana A. (International Review of Management and Marketing, 2016)
The relevance of the study is conditioned by the need of the society in the training of professionals, not only competitive on the labor market, but also patriots of their homeland, aware of the civil responsibility for the implementation of rights and duties, able to perform their civic duty. The purpose of the paper is to identify the features of pedagogical management of students’ civil and Patriotic qualities’ formation. The leading method is the method of action research (AR), allowing to obtain new knowledge about the pedagogical management of the process of students’ civil and Patriotic qualities’ formation characterizing their owners as civil society’s actors who are ready to serve and protect the homeland, to take conscious and active participation in the establishment of peace, mutual understanding and confidence between peoples, to respect for human rights. The article reveals the essence of civil-Patriotic education and justifies its concrete historical content; identifies the factors (student’s age, which is characterized by the pursuit to self-realization; features of humanitarian knowledge, as a component of educational content, including values, meanings, point of life), and pedagogical conditions (activation of the personal-semantic sphere of students; the revival of the ideas of the national school; ensuring of the impact of education on socialization) to manage the students’ formation of civil and Patriotic qualities; proposes the idea of the organization of students’ civil and Patriotic tours. The paper submissions can be useful for teachers of research universities; experts of centers for professional training and retraining of personnel in the selection and structuring of the content in the training of scientific and pedagogical staff of research universities. Keywords: Pedagogical Management, Civil-Patriotic Education, Civil and Patriotic Qualities, Personality-Semantic Sphere. JEL Classifications: A23, I23, I26